Characterization of the tetracycline resistance gene of plasmid pT181 of Staphylococcus aureus. - Mojumdar, M (1988)
Some genetic and biochemical properties of the tetracycline resistance element of the Staphylococcus aureus plasmid pT181 have been studied. Resequencing of a portion of the tetracycline resistance gene (tet) showed the presence of a single open reading frame of 1,299 nucleotides capable of encoding a polypeptide of 433 amino acids. Analysis of BAL 31 nuclease-generated deletion mutants of the tet gene showed the presence of two complementation groups within this region. Northern blot hybridizations demonstrated that the tet gene encodes a single mRNA, and its initiation site has been mapped by S1 nuclease protection experiments. We also identified an approximately 52,000-dalton tetracycline-inducible polypeptide in Bacillus subtilis minicells carrying pT181. Induction of the tet gene by tetracycline resulted in a 4-fold increase in the levels of TET mRNA and at least a 15-fold increase in the amount of TET protein in B. subtilis minicells.